Insulin-like growth factor 1 and insulin-like growth factor binding protein 2 serum levels as potential biomarkers in differential diagnosis between chronic pancreatitis and pancreatic adenocarcinoma in reference to pancreatic diabetes - Włodarczyk, Barbara; Borkowska, Anna; Włodarczyk, Przemysław; Małecka-Panas, Ewa; Gąsiorowska, Anita (Przegląd gastroenterologiczny, 2021)
Insulin-like growth factor 1 (IGF-1) has been connected with development of pancreatic ductal adenocarcinoma (PDAC). To evaluate the serum concentration levels of IGF-1 and insulin-like growth factor binding protein 2 (IGFBP-2) in patients with chronic pancreatitis (CP) and PDAC. Their values in diabetes mellitus (DM) were also assessed. The study included 83 patients with CP, 92 patients with PDAC, and 20 subjects as a control group. The concentrations of IGF-1 and IGFBP-2 were estimated with ELISA (Corgenix UK Ltd, R&D Systems). The IGF-1 was higher in CP compared with PDAC (81.11 ±57.18 ng/ml vs. 53.18 ±36.05 ng/ml, < 0.001), and both CP and PDAC were different from controls (81.11 ±57.18 ng/ml vs. 70.66 ±16.57 ng/ml, < 0.001 and 53.18 ±36.05 ng/ml vs. 70.66 ±16.57 ng/ml, < 0.001). CP without cysts have lower IGF-1 compared to those with CP and cysts (60.35 ±34.68 ng/ml vs. 93.55 ±64.78 ng/ml, < 0.05). IGF-1 in CP without DM was higher compared to IGF-1 in PDAC without DM (91.13 ±65.48 ng/ml vs. 54.75 ±40.41 ng/ml, < 0.001). In CP and DM the IGF-1 was elevated in comparison to PDAC and DM (62.20 ±32.38 ng/ml vs. 48.45 ±24.88 ng/ml, < 0.05). IGFBP-2 was higher in CP compared to PDAC (512.42 ±299.77 ng/ml vs 301.59 ±190.36 ng/ml, < 0.001). In CP and PDAC the IGFBP-2 level was elevated compared to the control group (512.42 ±299.77 ng/ml vs. 51.92 ±29.40 ng/ml, < 0.001 and 301.59 ±190.36 ng/ml vs. 51.92 ±29.40 ng/ml, < 0.001). IGFBP-2 in CP without DM was higher compared to PDAC without DM (559.39 ±281.43 vs. 296.53 ±196.93, < 0.001). IGF-1 and IGFBP-2 may be biomarkers of CP and PDAC. IGF-1 may be an indicator that signals whether pancreatic diabetes is from CP or PDAC.